ANALISIS MUTU KUALITAS PELAYANAN PADA KONSUMEN RUMAH MAKAN KAPAU PAK NIN BATAM - Wahyudi Ilham; Tito Pratama; Dailami (JURNAL MENATA, 2022)
In this study, the authors used a qualitative approach with a descriptive method. The sampling technique used in this research is purposive sampling. In purposive sampling technique. primary data sourced from field data collected directly by researchers at the restaurant "Kapau Pak Nin". The description of the research results was compiled based on the results of observations, unstructured interviews and documentation. Based on the results of the analysis that the researchers did in the form of observations, interviews, and documentation. Most of the resource persons gave good and quite good responses to the service quality of the Nasi Kapau Pak Nin restaurant. Reliability (Reliability), which can be said to be not completely good, Responsiveness (Responsiveness), which is already good. Assurance, which is very good because employees have good work skills and knowledge. Empathy (Empathy), which can be said to be good. Tangible (tangible), which can be said to be not entirely good.